Number 47 (June 2004) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 2004)
(June 2004) - Observations of watersnake (Nerodia, Colubridae) predation on darters (Percidae). By Melvin L. Warren, Jr., Wendell R. Haag, and Amy M. Commens Regional Southeastern Fishes Council Reports
Keywords: watersnake; nerodia; colubridae; predation; darters; percidae